2019
DOI: 10.20944/preprints201910.0349.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybrid Machine Learning Model of Extreme Learning Machine Radial Basis Function for Breast Cancer Detection and Diagnosis: A Multilayer Fuzzy Expert System

Abstract: Mammography is often used as the most common laboratory method for the detection of breast cancer, yet associated with the high cost and many side effects. Machine learning prediction as an alternative method has shown promising results. This paper presents a method based on a multilayer fuzzy expert system for the detection of breast cancer using an extreme learning machine (ELM) classification model integrated with radial basis function (RBF) kernel called ELM-RBF, considering the Wisconsin dataset. The perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…In this paper, the confusion matrix is used to evaluate the proposed models [37]- [39], [52]. This matrix includes 4 elements, including True Positive (TP), False Positive (FP), True Negative (TN) and False Negative (FN).…”
Section: Methods Evaluationmentioning
confidence: 99%
“…In this paper, the confusion matrix is used to evaluate the proposed models [37]- [39], [52]. This matrix includes 4 elements, including True Positive (TP), False Positive (FP), True Negative (TN) and False Negative (FN).…”
Section: Methods Evaluationmentioning
confidence: 99%
“…4 out of 7) and three models have been developed to address problems related to e-commerce, namely order arrival prediction, dynamic credit risk evaluation, and product recommendation. [6]. There is much evidence in the literature that ensemble classifiers and ensemble learning systems have been very effective in financial time series data.…”
Section: Hybrid Machine Learning Methodsmentioning
confidence: 99%
“…The evolution of DS methods has progressed at a fast pace, and every day, many new sectors and disciplines are added to the number of users and beneficiaries of DS algorithms. On the other hand, hybrid machine learning models consist of two or more single algorithms and are used to increase the accuracy of the other models [6,7]. Hybrid models can be formed by combining two predictive machine learning algorithms or a machine learning algorithm and an optimization method to maximize the prediction function [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This made Chicco and Jurman [3] to use machine learning methods to predict survival of patients with heart failure in which their results showed that serum creatinine and ejection fraction alone are enough to predict mortality of heart failure. However, major challenges in model learning is the feature selection problem, as the feature selection step is so important in machine learning with the purpose of eliminating unnecessary and unimportant features [9,[14][15][16] and also dealing with imbalanced dataset. It is not always possible to generate a good predictive model for imbalance dataset; approaches have been proposed to this issue in which we try to use in this paper in order to address the problem.…”
Section: Introductionmentioning
confidence: 99%